KONSEP BILANGAN RASIONAL DALAM AL-QUR’AN DAN HUBUNGANNYA DENGAN NILAI-NILAI RELIGIUS - Nasution, Sri Wahyuni (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2017)
Science all comes from the Qur'an, but many still doubt and even argue that science and the Qur'an are systematically integrated. Because of this problem, the writer wants to prove the relationship between the Qur'an and science is perfectly integrated by examining "The Concept of Rational Numbers in the Qur'an and its Relationship with Religious Values". So from this problem the author makes two formulations of the problem, namely: how is the concept of rational numbers in the Qur'an? and what is the relationship between the concept of rational numbers and religious values? The purpose of the author examines the formulation of the problem, namely: to know the concept of numbers in the Qur'an and to know the relationship between the concept of numbers and religious values. The usefulness of research for Islamic education institutions can be used as a source of knowledge and grip, while for educators this research is expected to be an alternative in improving cognitive values and religious values of children, and for students is expected to increase their pride and faith as Muslims and can prefer mathematics, as well as for researchers to know the concepts of rational numbers in the Qur'an and the concept of rational numbers in contemporary mathematics and their relationship to religious values.The theories used in this study are theories about rational number systems in the fields of mathematics, religious theories and philosophical sciences and the application of the Qur'anic ulul theory as a supporter of author research. This type of research is Library Research research using descriptive approaches, maudu'i interpretations, deductive thinking, inductive thinking, and philosophical approaches.The results of the research that the authors get are: the concept of numbers in the Qur'an is also a concept of numbers in Arabic. Rational numbers in the Qur'an are partially studied in text, and therefore use contextual understanding, for example by interpreting zero numbers (0) and mathematical lexical concordances, namely in the form of the relationship of words per word in the Qur'an by using the book Al-Mu'jam Al-Mufarash. In the concept of rational numbers in the Qur'an there is a relationship that is proven to be perfectly integrated and there are religious values in the form of: the belief in the existence of Allah SWT, self-awareness as a servant of Allah, and gratitude for the blessings of Allah. All of this is to describe the power of Allah SWT from the translation of related theories. The results of the discussion are in the form of a relationship in the Qur'an with religious values which can be seen from the interpretation of words from the word "number" to the reference of numbers from rational fractions to the largest number, namely "100,000" which is interpreted in the form indicator of religious value, namely: value gives a purpose or direction of value to give aspiration, value directs someone to behave, value is attractive, value disturbs feeling, and value is related to belief and trust. Because all the words interpreted from the Al-Qur'an translation all have indicators of religious value of at least one indicator, it can be concluded that the concept of rational numbers in the Qur'an has a relationship with religious values.